Epidemiological aspects of nephrolithiasis and chronic diseases of the cardiovascular system combination - R. V. Royuk; S. K. Yarovoy; N. A. Guseva; Sh. L. Voskanyan; V. V. Royuk; D. B. Rodin (Исследования и практика в медицине)
Purpose of the study. To analyze prevalence and characteristics of the cardiovascular diseases (CVD) in patients with urolithiasis, revealed for the first timeMaterials and methods. In a period between 2009 and 2018, was made a retrospective analysis of medical histories of 2311 patients with urolithiasis, which were treated in in the urology departments of the branch No. 1 of the MCHG named after N.N. Burdenko (n=1487) and GBUZ MO Krasnogorsk City Hospital No. 1 (n=824). In 67,6% of the cases (1562 patients) the diagnosis of urolithiasis was diagnosed for the first time on admission. Isolated urolithiasis was recorded in 676 cases (43,3%), in other 154 cases (9,8%) nephrolithiasis was combined with different variants of cardiovascular diseases (CVD) and diabetes. From 732 respondents with urolithiasis and associated cardiovascular diseases (CVD), were formed 3 groups, in the first group (I) were included patients (n=363) with hypertension and arterial hypertension: the second group (II; n=79) was formed from patients with isolated coronary heart disease. In the third group (III) were included 290 patients which had urolithiasis combined with hypertension, arterial hypertension and coronary heart disease. The stages of hypertension and degree of expression of arterial hypertension were given according to the recommendations of Russian science society of cardiology (2004). Stages of congestive heart failure were defined according to c NYHA (New York Heart Association) classification. Functional class of stable angina was defined according to Canadian Cardiovascular Society classification (1970,1976). The obtained data was analyzed using descriptive statistics methods.Results. Average age of patients was 65,4 +– 3,27; 78% of the patients were men. On an emergency basis were hospitalized 30,9% from group I, 27,6% from group 2, and 31,3% from group III. In group I more often were recorded hypertension I + arterial hypertension I (32,5%) and hypertension II + arterial hypertension II (40,2%). In group II effort angina was recorded in 30 cases (38%). Congestive heart failure occurred among 153 patients (20,9%); most often it occurred among patients from III – in 102 cases (35,2%). In the whole sample, congestive heart failure of I and II degrees prevailed – in 88 (12%) and 57 (7,9%) patients. Kidney stones were found in 59,4% of patients, in the ureters – in 30,9% of patients, in kidneys and in the ureters – in 9,9% of patients. Share of the patients with kidney stones in the shape of corals is 3,4% of the whole sample. Average sizes of kidney stones of the patients with congestive heart failure are 9,2–11,8 mm which is different from the sizes in whole sample – 6,9–9,5 mm.Conclusion. During the observation period, share of the patients with first time revealed urolithiasis, complicated with the cardiovascular diseases (CVD) increased in 1,9 times (16,7 versus 31,7%). Congestive heart failure, which was registered in 20,9% of patients, was charged with I and II degrees. The presence chronic cardiovascular diseases (CVD), especially complicated by congestive heart failure in patients with first time revealed nephrolithiasis, implies changes in the algorithms of metaphylactic of nephrolithiasis (regime of water loads, selection of diuretics and anticoagulants).